Extremely Thin Al2O3 Surface‐Passivated Nanocrystalline ZnO Thin‐Film Transistors Designed for Low Process Temperature. Issue 4 (25th January 2016) - Ahn, Cheol Hyoun; Kim, So Hee; Kim, Yong‐Hoon; Cho, Hyung Koun
Abstract : Nanocrystalline ZnO ( nc ‐ZnO) thin‐film transistors (TFTs) exhibit inherent instability under bias/photo stresses, which originates from the oxygen molecules adsorbed on the surface of the crystal grains. The space charge region at nanocrystal surfaces that is induced by adsorbed oxygen molecules produces a high electrical potential barrier and significantly interrupts charge transport between the source and drain in nc ‐ZnO TFTs. In this article, we developed high‐performance TFTs via the continuous deposition of an extremely thin Al2 O3 layer on a nc ‐ZnO channel. These devices were fabricated by atomic layer deposition at an extremely low process temperature of 150°C, including both the deposition and postannealing temperatures. The nc ‐ZnO TFT with an extremely thin Al2 O3 layer (1.8 nm) showed a significantly higher mobility (25 cm 2 /Vs) compared to devices without an Al2 O3 layer (3.6 cm 2 /Vs). This dramatic difference was ascribed to the suppression of the chemisorption of oxygen molecules at the nanocrystal surface during thermal annealing (reducing the potential barrier width/height between adjacent nanocrystals). Furthermore, ultrathin Al2 O3 ‐covered nc ‐ZnO TFTs exhibited considerably enhanced electrical/photo stability due to the reduction in adsorption/desorption events of oxygen molecules on the nanocrystal surfaces (with no change in the depletion width after illumination) under gate bias or illumination stress.